PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS XI SMAN 1 KUBU PADA MATERI SIFAT ELASTISITAS BAHAN - Nurasyiah, Nurasyiah; Yennita, Yennita; Syahril, Syahril (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This study aims to describe the cognitive learning outcomes of students with learning models using creative problem solving learning models in the material Elasticity Properties of Materials and To find out the cognitive learning outcomes of students using creative problem solving learning models in the material Elasticity Properties of Materials for class XI SMA Negeri 1 Kubu with class who apply conventional learning. The research was conducted on students in class XI SMA Negeri 1 Kubu on the material elasticity of the material, the classes taken were class XI IPA 2, which consisted of 28 students and class XI IPA 1, which consisted of 33 students where the two classes consisted of an experimental class and a control class. . The data collection instrument was in the form of a post-test results test for understanding the concept of material elasticity properties for class XI high school which consisted of 12 objective questions. The type of research used in this study was a quasi experiment and the research design used in this study was the Posttest Only Control Group Design. This type of research is a quasi-experimental design with Posttest Only Non-equivalent Control Group Design. The independent sample t-test with the help of SPSS version 21 shows that the creative problem solving learning model has an effect on students' cognitive learning. The students' cognitive learning outcomes in the experimental class were better than the control class. Furthermore, the average value of the experimental class was 81,85 and that of the control class was 73,48. These results indicate that the creative problem solving learning model is effective on students' cognitive learning outcomes.